Rola biegłych rewidentów w procesie współpracy z kontrolą wewnętrzną i nadzorem bankowym - Niewiadoma, Maria (The Role of the Auditors in the Process of Cooperation With the External Control and the Internal Control in Commercial Banks, 2005)
The control of financial statements by the auditors in banks and in Consolidated banks is the complicated problem. The article presents questions with possibilities practical cooperation between internal controls with external controls and auditors which has based on the New Banking Law and principles from the Basil Committee for Banking Control.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 146-158